Aplikasi Bakteri Penambat N (BPN) dan Pupuk Kotoran Sapi (PKS) pada Fitoremediasi Tanah Tercemar Minyak Bumi - Ibnu Rizki Perdana; Tualar Simarmata; Pujawati Suryatmana (University of Insan Cendekia Mandiri, 2020)
Biostimulants plays an important role in the phytoremediation process of soil contaminated with hydrocarbon compounds. This experiment aims to determine the best treatment between N-fixing bacteria (BNF) and cow manure (CM) that can improve oil-polluted soil. The experiment was conducted in January-April 2019 at Kebun Percobaan Ciparanje Fakultas Pertanian Universitas Padjadjaran, Jatinangor, Sumedang, used a randomized block design method with four combinations (without BNF + without CM, Azotobacter sp. + without CM, without BNF + CM dose of 100% and Azotobacter sp. 4% + CM dose of 100%). The results showed there was not significant with control, except combination of without BNF + CM dose of 100% treatment could increase the population of Azotobacter sp. of 4.8 x 108 CFU/g, while Azotobacter sp. + without CM can increase the degradation of hydrocarbons and dry weight of ramie plants 0.1047 ppm/day and 40.433 g.